EVALUASI KEPUASAN PENGGUNA DAN EFEKTIVITAS WEBSITE PENDAFTARAN DALAM TRANSFORMASI PROSES PENERIMAAN SISWA BARU: Evaluation of User Satisfaction and the Effectiveness of the Registration Website in the Transformation of the New Student Admission Process - Badrudin, Muhamad Badar; Rohayani, Ai (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
Digital transformation in education has encouraged educational institutions to adopt information technology to enhance efficiency and transparency, one of which is through the use of student registration websites. This study aims to evaluate user satisfaction and the effectiveness of the student registration website in the new student admission process at Pondok Pesantren Darussalam Kasomalang Subang West Java. This research uses a qualitative approach with a case study method, involving observations and interviews with the primary users of the website, namely prospective students and parents. The results indicate that while users are satisfied with the ease of access and information transparency, there are some challenges related to access speed and dependence on internet connectivity. Furthermore, the registration website has been proven to improve data efficiency and accuracy, although it still requires technical improvements to optimize its functionality. These findings contribute to the literature on the application of technology in education, particularly in managing student registration administration. Practically, this research provides recommendations for Islamic educational institutions to continue improving web-based information systems to be more responsive and efficient.